DNA barcoding, species-specific PCR and real-time PCR techniques for the identification of six Tribolium pests of stored products - Zhang, Tao; Wang, Yi-Jiao; Guo, Wei; Luo, Dan; Wu, Yi; Kučerová, Zuzana; Stejskal, Václav; Opit, George; Cao, Yang; Li, Fu-Jun; Li, Zhi-Hong (Scientific reports, 2016)
Flour beetles of the genus Tribolium Macleay (Coleoptera: Tenebrionidae) are important stored product pests in China and worldwide. They are often found or are intercepted in grain depots, flour mills, and entry-exit ports, etc. Traditionally, Tribolium species are identified according to the morphological characteristics of the adult. However, it is almost impossible to rapidly identify adult fragments and non-adult stages based on external morphological characteristics. Molecular techniques for the rapid and accurate identification of Tribolium species are required, particularly for pest monitoring and the quarantine of stored products pests. Here, we establish DNA barcoding, species-specific PCR, and real-time PCR techniques for the identification of six stored-product pest Tribolium species including T. castaneum, T. confusum, T. destructor, T. madens, T. freemani and T. brevicornis. We detected the mitochondrial DNA cytochrome oxidase subunit I (COI) barcodes for Tribolium from 18 geographic populations and 101 individuals, built a Tribolium DNA barcode library, and designed species-specific primers and TaqMan probes for the above six Tribolium species. The three techniques were applied to identify Tribolium collected from stored samples and samples captured from quarantine ports. The results demonstrated that three techniques were all able to identify the six species of Tribolium both rapidly and accurately.
Keywords: Animals; taxonomické DNA čárové kódování; Base Sequence; DNA Barcoding, Taxonomic; Electron Transport Complex IV; druhová specificita; DNA; respirační komplex IV; Species Specificity; DNA primery; Phylogeny; Sequence Alignment; sekvence nukleotidů; Tribolium; DNA Primers; zvířata; fylogeneze; kvantitativní polymerázová řetězová reakce; sekvenční seřazení; Real-Time Polymerase Chain Reaction